Selected Shorts 2 Award Winning European Shorts - Widrich, Virgil; Wald, Micha; Ellis, Sean (Selected Shorts, 2005)
A selection of 10 multiple awarded European Shorts, amoung them a serie of shorts that won a jury- or audience award at the ISFFL. [www.kortfilmfestival.be]